PEMBERDAYAAN MASYARAKAT DI DESA SIDOREJO KABUPATEN PURWOREJO MELALUI PENGUATAN KELEMBAGAAN BERBASIS PENGEMBANGAN POTENSI LOKAL - Nur Feriyanto (Asian Journal of Innovation and Entrepreneurship, 2016)
With the enactment of Law No. 6 of 2014 on the village then became a tremendous opportunity for every village in Indonesia to be able to develop all their potential independently according to the needs of each in order to realize the public welfare. Law number 6 th 2014 Article 4 is to encourage initiative, movement, and the participation of the village community to the development potential and assets for the welfare of the village together; as well as improve the economy of the village community and overcome the gap of national development. But this time there is very little village that is able to develop its potential. It is due to this village for more positioned as the object of development so it relied on the help of the central government. Low creativity of human resources in the village as a result of the development system is centralized in the past resulted in a lot of potential left to rot is not developed to the source of the prosperity of society. In an effort to manage the existing potential, the necessary institutional strengthening through the establishment of institutional capacity building in a professional, efficient, effective and responsible so as to improve the economy of the community and solve the problems of poverty that has been happening.